Pelatihan Kompetensi Jaringan Wireless Optical untuk Meningkatkan Kesiapan Kerja Siswa SMK Nusantara 1 Kota Tangerang - Yus Natali Natali; Ade Nurhayati; Seshariana R. Melati; Alva N. Sularso; Hesmi A. Yanti; Habib N; Atilla P. Nugroho; Rafly F. (Universitas Negeri Gorontalo, 2026)
The rapid development of fiber-optic and wireless communication technologies has increased the demand for vocational graduates with competencies aligned to the needs of the telecommunications industry. However, practical competencies in Cisco-based network configuration and fiber-optic measurement remain limited among vocational high school students. This community service program aimed to strengthen the competencies of students at SMK Nusantara 1 Tangerang City through practice-based wireless–optical network training. The program involved 113 students from the Computer and Network Engineering program and integrated conceptual learning, Cisco network configuration, fiber-optic measurement, demonstrations, and hands-on practice. Program evaluation was conducted through observations and questionnaires completed by 56 participants. The findings indicate improvements in participants' understanding of wireless–optical networking concepts, basic Cisco network configuration, and fiber-optic measurement skills. Questionnaire results also revealed positive responses toward the relevance of the training materials, learning methods, instructor support, and the need for similar programs in the future. The program contributes to strengthening students' vocational competencies and supports their work readiness by providing practical experience relevant to current telecommunications industry requirements.